SIFAT FISIK TANAH PADA HUTAN TANAMAN KEMIRI, LAHAN AGROFORESTRI DAN LAHAN HUTAN SEKUNDER DI DESA LABUAN KUNGGUMA KABUPATEN DONGGALA SULAWESI TENGAH - Lapadjati, Karsapakyawan K.; Wardah, Wardah; Rahmawati, Rahmawati (Universitas Tadulako, 2016)
The aim of this research was to find the physical characters of the soil in candlenut forest, agroforestry and secondary forest area at Labuan village Kungguma Donggala District of Central Sulawesi. This research was begun from location orientation, deciding three swath spots which were: candlenut forest, agroforestry area (teak and cocoa) and secondary forest. In deciding the location, purposive sampling was applied. From three locations, 5 samples of soil were taken so that there were 15 samples of soil taken. From five soil samples of one sample location were composed into one soil sample for next three soil samples analyzed in Geology laboratory. The result of the research showed that the conversion of the secondary forest into agroforestry and candlenut forest could reduce the physical characters of the soil (permeability, porosity, Bluk density, and organic material of the soil). Besides that, the texture of the soil in candlenut forest, agroforestry and secondary forest were different; they were sandy clay, dusty clay and clay.Kata Kunci: Physical properties, Candlenut, Secondary Forest, Agroforestry